Sosialisasi Dan Praktik Pembuatan Silase Dan Mineral Molase Blok Oleh KKN UNS 129 Sebagai Solusi Pakan Ternak Desa Gendayakan - Suryadi Budi Utomo; Rizki Ramadhan; Aditya Mahendra; Laelatur Rosyidah (KREASI : Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2022)
The biggest problem in raising ruminants is the issue of providing quality animal feed facilities at competitive prices and can be made available forever. The cost of animal feed can reach about 60% to 80% of the cost of production. The strategy for providing animal feed, among others, is to provide animal feed in the form of concentrate and UMMB (Urea Mineral Molasses Block) feed and the strategy of providing animal feed can also be done using the silage method. The purpose of socialization and practice of making silage and MMB to the community is so that the people of Gendayakan Village can know firsthand both in theory and practice about how to make silage and MMB so that the knowledge received is expected to be useful and implemented later by residents. The method in community service that we do is a descriptive method by conducting outreach to the community in Gendayakan Village. The results of this service activity show that the Gendayakan Village community is able to choose quality feed ingredients, namely silage and UMMB and livestock kept by partners show an increase in production before and after the activity, farmers are asked to fill out a questionnaire with the aim of knowing the level of understanding of farmers about the procedure feed processing before and after activities.